Práticas de marketing digital: estágio na empresa Weboost - Matias, Diana Figueiredo (2022)
The report presents some concepts within the area of digital marketing, namely social networks, content marketing and email marketing, in order to understand their application in the context of digital marketing. Additional importance was given to the creation of content and the description of the tasks that are performed at Weboost – Digital Marketing Agency. The internship's professional experience allowed the application of digital marketing knowledge in the creation of content for social networks for several of the company's clients. From monthly planning (choosing the theme of each publication and developing copies), blog articles, content scheduling, email marketing, benchmarking, website optimization through keywords and meta descriptions (SEO) to customer contact.